Hubungan Kinerja Guru dengan Hasil Belajar Fisika Siswa SMA se Kota Kendari - Suayib, Laode; Anas, Muhammad; Arisona, Arisona (Jurnal Penelitian Pendidikan Fisika, 2020)
The objective of this study is to describe the relationship between teacher performance and learning outcomes in high school students in Kendari. The research method used is descriptive correlative with the sampling technique using proportionate stratified random sampling. The research instrument is using a questionnaire of physics teacher for grade XII high school and the results of national exam the 2018/2019 academic years, by respondents consisting of 15 teachers and 692 students. Data analysis uses pearson product moment correlations. The results are showed that teacher performance has a linear correlation of student learning outcomes with a correlation value (r) of 0.533 or 53.33% and 46.67% determined by other factors such as: the hierarchical relationship between the head master by teachers and staff, who are not established yet. On the other hand, management of school organization is not optimal. The results of this study can be used as a basic for policy making for the Education and culture office in Kendari city to apply the relationship patterns ofÂ  teacher performance and student learning achievement.